Child Pugh C and Male Gender were Related to Nutritional Status of Liver Cirrhosis Patients in Koja Hospital Jakarta - Suzanna Ndraha; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2009)
Background: Malnutrition is found in 65-90% patients with liver cirrhosis. Malnourished patients with cirrhosis have a higher rate of complications. Aim of this study was to evaluate the prevalence and risk of malnutrition in liver cirrhosis patients at Koja hospital, Jakarta. Method: All liver cirrhosis patients visited Koja hospital during January - March 2009 was evaluated. An inclusion criterion was liver cirrhosis. An exclusion criterion was unable to speak Indonesia. The distributions of age, gender, body mass index (BMI), triceps skin-fold thickness (TSF), mid-upper arm circumference (MUAC), mid-arm muscle circumference (MAMC), Child Pugh classification were assessed. The criteria of malnutrition was done according to MAMC and BMI. Result: There were 38 liver cirrhosis patients fit the criteria. Twenty five (65.8%) cases were classified as malnutrition according to MAMC, 21 (55.3%) were classified as malnutrition according to BMI. Four patients (10.5%) were Child Pugh scores A, 15 Child Pugh B (39.5%) and the rest 19 patients (50.0%) were Child Pugh C. There was a trend correlation between malnutrition according to MAMC and Child Pugh criteria but not statistically significant. Conclusion: In our study we found 65.8% of liver cirrhosis patients were malnourished according to MAMC. Malnutrition was higher in male, as well as in Child Pugh score C. MAMC is more accurate than BMI in assessing nutritional status in liver cirrhosis. Keywords: liver cirrhosis, nutritional status, MAMC, BMI, Child Pugh score